Interim results of selective screening using whole exome sequencing in newborns - G. P. Bogonosova; O. V. Bugun; S. V. Ionushene; T. A. Astakhova; I. M. Golobkova; A. A. Dokshukina; Je. Shubina; T. A. Bairova; D. N. Degtyarev; D. Yu. Trofimov; L. V. Rychkova; N. N. Martynovich; et al. (Acta Biomedica Scientifica, 2025)
Background. Evaluation of hereditary diseases is a difficult task due to the large number of nosologic forms, rare occurrence of each disease, which can lead to a long diagnostic search for the patient. Different methods of molecular genetics, including full-exome sequencing, are actively introducing into the complex of examination of newborns with general pathology and lead to better diagnosis and prognosis for children and their families.The aim of the study. To estimate the frequency of occurrence of genetic disorders in newborns with somatic and surgical pathology during selective screening using whole exome sequencing.Materials and methods. Within the  framework of  the  regional pilot project on selective exome screening of newborn children, which is carried out on the basis of the National Medical Research Center for Obstetrics, Gynecology and Perinatology named after Academician V.I. Kulakov, we estimated the results of genetic evaluation of 80 newborns who were treated in the neonatal departments of the Ivano-Matreninskaya City Children’s Clinical Hospital from February to October 2024.Results. Eighty children were examined. Genetic findings of varying significance were detected in  31.2  % of  the  examined children. Pathogenic and likely pathogenic gene variants were detected in 16.2 % of cases, and chromosomal aberrations in  2.5  % of  patients. Genetic findings of  varying significance were found in  52  % of those examined for nervous system damage and in 18 % of patients with congenital malformations. By the time of description, the genetic diagnosis was confirmed in 16.2 % of patients with genetic findings. The diagnosis was based on the complete correspondence of the child’s existing phenotype with the identified gene variant.Conclusions. The results of this study indicate a possible high incidence of exome abnormalities in neonatal pathology, as well as the high efficiency of whole exome sequencing in their diagnosis.